Pengaruh Minat dan Persepsi Profesi Guru Terhadap Kesiapan Menjadi Guru Produktif Mahasiswa Program Studi Kependidikan - Sunardi Sunardi; Rahmad Syarifudin; Buyung R. Machmoed (Universitas Negeri Gorontalo, 2023)
The interest in becoming a teacher and the perception of the teacher profession are important factors to support the readiness of students to become productive teachers in the educational study program at the Faculty of Tenik, Gorontalo State University. The objectives of this study are: (1) Analyzing the influence of interest on readiness to become productive teachers for students of the Education Study Program at the Faculty of Engineering, Gorontalo State University (2) Analyzing the influence of teacher professional perceptions on readiness to become productive teachers of students of the Education Study Program at the Faculty of Engineering, Gorontalo State University (3) Analyzing the influence of interest and perception of the teacher profession simultaneously on readiness to become productive teachers for program students. Educational Studies at the Faculty of Engineering, Gorontalo State University. This type of research is associative to look for the influence of the interests and perceptions of the teacher profession on the readiness of students to become productive teachers. The population of this study is all students of the educational study program at the Faculty of Engineering, Gorontalo State University Batch 2017 - 2018, a total of 216 people, the ideal number of samples using the Slovin formula is 140 people. Using data collection techniques through questionnaire deployment, and data analysis techniques through simple regression and multiple regression. The results show that there is a positive influence of interest and perception of the teacher profession on the readiness to become productive teachers for students of the Education Study Program, by 17.9% on readiness to become productive teachers.